IDENTIFICATION OF ENTEROTOXIGENIC STAPHYLOCOCCI IN MEAT RAW MATERIALS - D. S. Bataeva; M. Yu. Minaev; A. A. Makhova (Теория и практика переработки мяса)
The need to renew the safety criteria for meat raw material used in production of fermented sausages was determined. The presence of the enterotoxigenic S. aureus strains in meat raw material was established. The method was mastered and the PCR approaches to identification and screenings of enterotoxigenic strains and their toxins in meat raw material were proposed. In order to identify enterotoxigenicity of detected staphylococci, the conservative regions of the S. aureus target gene sequences responsible for production of different types of enterotoxins (A, B, Е, С, D) were found and studied. In addition, short fragments of a nuclear acid (primers) corresponding to these revealed genes were constructed. As a result of identification, it was established that two isolated strains of S. аureus were enterotoxigenic. One of them produced type А and Е toxins (strain NG1) and another produced type С and Е toxins (strain NG2). The sensitivity and specificity of the real-time PCR method allowed not only identification of pure cultures but also screening of enterotoxigenic strains and their toxins in a product. The use of this method in the production control for the presence of the enterotoxigenic strains of S. aureus in meat raw material used in fermented sausage manufacture was recommended.